2022
DOI: 10.1177/2632010x221124908
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the SARS-CoV-2 Omicron (B.1.1.529) Variant and Emerging Impact on Global Public Health

Abstract: The discovery of the SARS-CoV-2 Omicron (B.1.1.529) variant has sparked alarm globally because of its rapid rate of infection and trespassing acquired immunity due to vaccination or natural infection. This heavily mutated variant is rapidly spreading around the world. Infected individuals with the Omicron variant may suffer from flu-like symptoms, and infected with the Delta variant frequently report low oxygen levels, high pulse rates, and a loss of smell and taste. Also, the Omicron variant causes asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…4 Omicron subvariants that have rapidly spread across the globe. 5 , 6 Initially, BA.1 and BA.2 were predominant Omicron subvariant worldwide. However, BA.4 and BA.5 variants are now leading in Europe and the United States.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…4 Omicron subvariants that have rapidly spread across the globe. 5 , 6 Initially, BA.1 and BA.2 were predominant Omicron subvariant worldwide. However, BA.4 and BA.5 variants are now leading in Europe and the United States.…”
Section: Introductionmentioning
confidence: 98%
“…Currently, the Omicron variant includes five lineages and some other descendant subvariants 4 . Omicron subvariants that have rapidly spread across the globe 5,6 . Initially, BA.1 and BA.2 were predominant Omicron subvariant worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists predicted from the beginning of the COVID‐19 pandemic that the mutant strains of the virus might elongate the pandemic 11–14 . Mutations of the SARS‐CoV‐2 are always going on.…”
Section: Sars‐cov‐2 Mutation From Alpha To Omicronmentioning
confidence: 99%
“…Although the transmissibility was increased, a declined trend was observed in hospitalization and mortality rates during Omicron according to the data 53 . For instance, in a retrospective cohort study, Nyberg et al 54 showed that compared with Delta, those with Omicron were at low risk of severe outcomes after SARS‐CoV‐2 infection with significant variation associated with age.…”
Section: Transmissibility and Severity Of The Omicron Variantmentioning
confidence: 99%